2020
DOI: 10.3897/mbmg.4.55162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of species gaps in DNA barcode libraries of non-indigenous species (NIS) occurring in European coastal regions

Abstract: DNA metabarcoding has the capacity to bolster current biodiversity assessment techniques, including the early detection and monitoring of non-indigenous species (NIS). However, the success of this approach is greatly dependent on the availability, taxonomic coverage and reliability of reference sequences in genetic databases, whose deficiencies can potentially compromise species identifications at the taxonomic assignment step. In this study we assessed lacunae in availability of DNA sequence data from four ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The depth and accuracy of DNA metabarcoding‐based identifications are mainly dependent on the availability of reference libraries containing representative and accurate sequences for the targeted species. The existence of gaps and unequal representation of taxonomic groups in reference databases may compromise the accuracy of the DNA‐based biodiversity assessments (Ardura, 2019; Duarte et al., 2020; Leite et al., 2020; Weigand et al., 2019). Thus, assessing these gaps and the quality of sequence data in reference databases is mandatory for the successful implementation of DNA‐based tools in biodiversity assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The depth and accuracy of DNA metabarcoding‐based identifications are mainly dependent on the availability of reference libraries containing representative and accurate sequences for the targeted species. The existence of gaps and unequal representation of taxonomic groups in reference databases may compromise the accuracy of the DNA‐based biodiversity assessments (Ardura, 2019; Duarte et al., 2020; Leite et al., 2020; Weigand et al., 2019). Thus, assessing these gaps and the quality of sequence data in reference databases is mandatory for the successful implementation of DNA‐based tools in biodiversity assessments.…”
Section: Introductionmentioning
confidence: 99%
“…43% and 34% were covered by sequences, in BOLD and PR2 databases, respectively (Rey et al 2020). Very recently, Duarte et al (2020), found that from the total number of species included in the AquaNIS and EASIN databases, occurring in European coastal regions, approximately 65% and 55%, respectively, had at least one of the searched barcode markers (COI, 18S, rbcL and matK), in BOLD or GenBank. However, the values of missing barcodes clearly differed among taxonomic groups (i.e.…”
Section: Incompleteness Of Reference Sequences Databases For Nismentioning
confidence: 99%
“…However, the values of missing barcodes clearly differed among taxonomic groups (i.e. Animalia, Chromista and Plantae) and the barcode markers searched (Duarte et al 2020). Definitely, expanding genetic databases with reference sequences is mandatory to make the most of the potential of the DNA metabarcoding approach in NIS surveillance in coastal ecosystems.…”
Section: Incompleteness Of Reference Sequences Databases For Nismentioning
confidence: 99%
“…We conducted a global gap-analysis by comparing the available barcoded species of Phyllodocida by 4 April 2020 and its congruence with the total number of valid species [24,59,60]. We compared the species list CL-MTVPP with all publicly available COI-5P sequence records using the BOLD checklist tool to obtain the percentage of barcoded species.…”
Section: Data Processing and Analysesmentioning
confidence: 99%
“…However, the number of studies dedicated to this annelid group and, consequently, that of the associated barcoding projects must also be taken into account [24]. For example, in the case of fishes, the amount of dedicated projects is significantly higher and, thus, the barcode library closer to completion [115][116][117], which is not the case for macroinvertebrate barcoding projects and the current state of its molecular libraries [60].…”
Section: Global Gap-analysismentioning
confidence: 99%